2003
DOI: 10.1002/immu.200310018
|View full text |Cite
|
Sign up to set email alerts
|

Mice transgenic for intracellular interleukin‐1 receptor antagonist type 1 are protected from collagen‐induced arthritis

Abstract: Interleukin-1 receptor antagonist (IL-1Ra) is a natural IL-1 inhibitor, which competitively inhibits binding of IL-1 to its receptors. IL-1Ra is produced as four different isoforms, one secreted (sIL-1Ra) and three intracellular (icIL-1Ra1, 2, 3), derived from the same gene. We previously observed increased production of icIL-1Ra1 in the joints of mice with collageninduced arthritis (CIA). However, due to its intracellular localization, the biological role of icIL1Ra1 remains unknown. The aim of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…For example, treatment of rheumatoid arthritis patients with chimeric mAbs to TNF-␣ significantly improved major clinical end points of the disease process, including a decrease in SAA (31). Transgenic mice overexpressing IL-1R antagonist were protected from collagen-induced arthritis, with reduced level of circulating A-SAA (32). We demonstrated that bortezomib can transiently inhibit the induction of luciferase expression at the knee joint after zymosan administration.…”
Section: Figurementioning
confidence: 79%
“…For example, treatment of rheumatoid arthritis patients with chimeric mAbs to TNF-␣ significantly improved major clinical end points of the disease process, including a decrease in SAA (31). Transgenic mice overexpressing IL-1R antagonist were protected from collagen-induced arthritis, with reduced level of circulating A-SAA (32). We demonstrated that bortezomib can transiently inhibit the induction of luciferase expression at the knee joint after zymosan administration.…”
Section: Figurementioning
confidence: 79%
“…For instance, a 67-amino acid sequence of MCP-1 that specifically antagonizes MCP-1 abrogated arthritis in MRL-lpr autoimmune mice, and an antagonist of RANTES ameliorated CIA in mice (47)(48)(49). IL-1 receptor antagonist protein, a naturally produced specific antagonist of IL-1␤, has consistently shown potent antiinflammatory properties in animal models of inflammation (50)(51)(52) and is used in the treatment of RA (53)(54)(55)(56)(57)(58). CXCL16 is a novel chemokine that has not been fully characterized in chronic disease, and it is especially of interest because its only known receptor to date has been shown to be highly expressed in chronic Th1 diseases such as RA (28).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from 1 · 10 6 BMMC, P815 cells, 3T3 murine fibroblasts, ATDC5 mouse chondrocytes or from joints of mice with collagen induced arthritis [13] with TRIzol (Invitrogen) according to the manufacturer's protocol.…”
Section: Rna Extractionmentioning
confidence: 99%